2007
DOI: 10.1007/s00595-006-3470-8
|View full text |Cite
|
Sign up to set email alerts
|

Portal Vein Thrombi After Ileal Pouch-Anal Anastomosis: Its Incidence and Association with Pouchitis

Abstract: Portal vein thrombi are a common finding in the subset of patients who require a CT scan after IPAA. Patients who suffer PVT have a higher incidence of postoperative pouchitis. Thus a prospective evaluation of the risk of PVT and its association with pouchitis is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 55 publications
0
44
1
Order By: Relevance
“…164 Portal vein thrombosis has been seen in UC patients following restorative proctocolectomy. [165][166][167] (Fig. 5).…”
Section: Portal Vein Thrombosis and Hepatic Abscessmentioning
confidence: 91%
See 1 more Smart Citation
“…164 Portal vein thrombosis has been seen in UC patients following restorative proctocolectomy. [165][166][167] (Fig. 5).…”
Section: Portal Vein Thrombosis and Hepatic Abscessmentioning
confidence: 91%
“…165 Thrombotic complications of IPAA may be associated with an increased risk for subsequent pouchitis, as a recent study reported that 45% of selected patients with perioperative portal vein thrombosis later developed pouchitis compared with 15.4% in patients without portal vein thrombosis. 167 The clinical significance of portal vein thrombosis and its effect on pouch and liver functions are under investigation by our team. …”
Section: Portal Vein Thrombosis and Hepatic Abscessmentioning
confidence: 99%
“…28,29 Asymptomatic portal vein thrombosis may occur in up to 40% of patients undergoing IPAA surgery. 30 The clinical spectrum associated with portal vein thrombosis is variable, ranging from subtle symptoms to fever, vomiting, abdominal distension, pain, and ileus. Indeed, portal vein thrombosis can present with severe pain imitating an acute abdomen and should always be considered in patients that deteriorate in the postoperative period, especially those who have already been discharged from the hospital.…”
Section: Small Bowel Obstructionmentioning
confidence: 99%
“…Furthermore, 2 patients in the study group had a history of perioperative portal vein thrombi treated with anticoagulant therapy, which has been reported to be associated with pouchitis. 41 Finally, the majority of patients with ischemic pouchitis in this study were male, suggesting that estrogen may not play a major role in pouch ischemia.…”
Section: Discussionmentioning
confidence: 96%